Dynamic effects of material production and environmental sustainability on economic vitality indicators: A panel VAR approach - Jo\~ao Leit\~ao; Joaquim Ferreira (Journal of Risk and Financial Management, 2021)
This study analyzes the relationships and dynamics between material production, foreign direct investment (FDI), economic activity, carbon productivity, the stock market, and green tech, both in a global and European context, using panel vector autoregressive methodology (PVAR). The empirical evidence obtained for the Global Group reveals four significant and positive unidirectional causality relationships, where aggregate material production is the prominent variable. For the EU-15 group, six significant causality relationships were detected, among them three negative and three positive unidirectional relationships. The stock markets shock reveals to be the most dominant variable, despite FDI standing out as causing the greatest shock effect. Nevertheless, in the European context, limited evidence of dematerialization is detected. Economic recessions show a generally negative effect, which contrasts with the economic Kitchin cycles, which reveal the effect of a generally positive relationship.
Keywords: 330; cycle; economic activity; environmental sustainability; materials; panel models; sustainable finance